The molecular pathogenesis of mantle cell lymphoma. Issue 7 (3rd July 2017) - Vogt, Niklas; Dai, Beiying; Erdmann, Tabea; Berdel, Wolfgang E.; Lenz, Georg
Abstract: Mantle cell lymphoma (MCL) is characterized by the translocation t(11;14) leading to constitutive cyclin D1 overexpression. However, overexpression of cyclin D1 alone is insufficient to cause malignant transformation. Secondary genetic alterations and deregulated signaling pathways involved in DNA damage response, cell proliferation, and apoptosis are indispensable for MCL lymphomagenesis. Recent studies investigating the biology of MCL have revealed crucial importance of B-cell receptor (BCR), nuclear factor-kappa B (NF-κB), phosphoinositide 3-kinase (PI3K), and BCL2 signaling for the molecular pathogenesis of MCL. In addition, activation of the Janus kinase (JAK)/signal transducer and activator of transcription 3 (STAT3), NOTCH and WNT pathway can be observed in subsets of MCLs. These addictions can potentially be utilized therapeutically by implementing small molecule inhibitors into current treatment regimens.